MEDIA PENYALURAN KAMPANYE MELALUI INSTAGRAM BSBI DALAM PROGRAM BEASISWA SENI DAN BUDAYA 2019 - Ni Putu Eka Budi Pradnya Wulandari Dewi; Nursyirwan Effendi; Emeraldy Chatra (Ensiklopedia of Journal, 2022)
Indonesian Arts and Culture Scholarship (IACS) that displays Indonesian arts, and culture is a program which is held by the Directorate of Public Diplomacy, the Ministry of Foreign Affairs of the Republic of Indonesia. This program was conducted face-to-face from 2003 to 2019. Through this program, a good opportunity is certainly obtained by Indonesia state to spread Indonesia cultural values. This research analyzes how Instagram can play an important role in promoting the 2019 IACS program so that, the general public can know about this program. This research was being analyzed by using Circuit of Culture model, and specified in Production moment. By analyzing Instagram, we can find out how the account is managed, and the content shared by the committee of IACS 2019. Data were taken based on interview, and social media. The results are MoFA doesn’t use Instagram @iacs_kemlu well. This can be seen from the minimal upload of documentation of the participants, and MoFA is not carrying out the monitoring function regarding the inactive @bsbi_pdg Instagram account. Besides that, on Instagram @iacs.banyuwangi, Instagram management is very lacking. It can be seen from @iacs.banyuwangi Instagram account page.